The Redefinition of the EU Presence in Latin America and the Caribbean - Gardini, Gian Luca (Peter Lang International Academic Publishers, 2023)
This book explores three key issues to understand the redefinition of relations between the European Union (EU) and Latin America and the Caribbean (LAC): the international context, foreign policies of EU member states towards Latin America, and crucial topics on the EU-LAC agenda. At the theoretical level, the book aims to rebalance two debates on EU-LAC relations. First, in the debate between agency and structure, the book stresses that context is a limiting factor of the agent's preferences and actions. Second, in the debate between values and interests, it finds that interests should not be made invariably dependent on values. At the empirical level, two aspects stand out. First, the change and continuity in EU member states' foreign policies also impact the EU's own role in the continent. Second, new topics on the bi-regional and global agenda have the potential to redefine the relations between the two regions. At a time of European alleged decline, this volume argues that the EU remains a highly significant actor in Latin America and the Caribbean. "EU-Latin American relations are in a phase of redefinition. This timely book addresses both the structural obstacles and the prospects and areas for deeper cooperation. Against the background of diverging positions of Latin America and the EU in international politics, the proposed decoupling of political and functional agendas should be considered." Detlef Nolte, German Institute für Global and Area Studies (GIGA) "This book makes an original and significant contribution to the study of the relations between the European Union and Latin American and the Caribbean. The volume blends wisely the right doses of scholarly research and policymaking sensitivity, thus making for an innovative read for academics and an insightful contribution for practitioners." Andrés Malamud, University of Lisbon